Employing Psychoacoustic Model for Digital Audio Watermarking - Chai Siew, Li (2013)
This thesis discusses about digital audio watermarking by employing psychoacoustic model to make the watermarked signal inaudible to the audience. Due to the digital media data able to distribute easily without losing of data information, thus the intellectual property of musical creators and distributor may affected by this kind of circumstance . To prevent this, we propose the usage of spread spectrum technique and psychoacoustic model for embedding process, zero-forcing equalization and detection and wiener filtering for extracting process. Three samples of audio signal have been chosen for this experiment which are categorized as quiet, moderate, and noise state signal. The findings shows that our watermarking scheme achieved the intended purposes which are to test digital audio watermarking by employing psychoacoustic model, to embed different length of messages to test on accuracy of extracted data and to study the suitability on using hash function for verification of modification attacks.